Wszędzie dobrze, ale w domu najlepiej. Analiza decyzji dotyczących kontynuacji nauki na studiach drugiego stopnia na podstawie danych rejestrowych Uniwersytetu Warszawskiego - Zając, Tomasz; Komendant-Brodowska, Agata (Wydawnictwo Naukowe UAM, 2016)
The aim of the paper is to analyse decisions of first degree graduates concerning continuation of their education on second-degree programmes. One of the changes introduced by the Bologna process was a division of university programmes for the first-degree (bachelor’s degree) and second-degree (master’s degree) programmes. As a result, a new educational threshold has appeared in the course of higher education and at that threshold students decide whether to continue education and if so, which university and programme to choose. All choices involve various costs and benefits, both to be experienced immediately, as well as those that students plan to achieve or incur in the future. The article presents data on the decisions regarding the continuation of studies in the context of the assumptions of rational choice theory: methodological individualism and rationality of actors. The analysed data come from registers of the University of Warsaw. The most common decision of first-degree graduates at the University is not to change anything: either the programme or mode of study. This result will be explained in the context of assumptions about the preferences of the students.
There is no Place Like Home. Analysis of the Decisions of First-Degree Graduates Concerning Continuing Education Based on Registers of the University of Warsaw
Keywords: second degree studies; sociology of education; educational choices; rational choice theory; register data analysis